TINJAUAN YURIDIS SENGKETA KEBIJAKAN EKSPOR NIKEL INDONESIA DI WTO DAN IMPLIKASINYA TERHADAP KEDAULATAN SUMBER DAYA ALAM NEGARA BERKEMBANG - Rahmat Giling; Annie Myranika; Nursalim; Mahmuddin; Dany Wahyu (CV. Lafadz Jaya, 2026)
This study analyses the dispute over Indonesia’s nickel ore export policy at the World Trade Organization (WTO), initiated by the European Union (DS592), as a paradigmatic case in the conflict between international trade obligations and developing countries’ sovereignty over natural resources. Using a normative-empirical legal research method, this article examines the WTO Panel’s November 2022 ruling and Indonesia’s appeal, and relates these to recent developments in the reform of Investor-State Dispute Settlement (ISDS) under UNCITRAL Working Group III. The study finds that this dispute illustrates a fundamental tension between GATT Article XX (general exceptions) and sustainable industrialisation policies. A comparative analysis with the Argentina Footwear and *China Raw Materials* cases demonstrates the evolution of WTO jurisprudence regarding natural resource conservation policies. Furthermore, this study critiques the deficiencies of the WTO Appellate Body and proposes a Multi-Party Interim Appeal Arbitration Arrangement (MPIA) as an alternative mechanism. The implications of this dispute extend to the realm of international investment arbitration, where similar policies could potentially give rise to *indirect expropriation* claims under Bilateral Investment Treaties (BITs). The study recommends harmonising natural resource industrialisation policies with WTO provisions through an integrated sustainable development approach, as well as Indonesia’s participation in the MPIA to ensure access to effective appellate review.